PERILAKU KONSUMTIF MAHASISWA TERHADAP KOMITMEN BELAJAR - Elisabeth Kawu; Mardi Lestari; Dhevy Puswiartika; Dian Fitriani (Berajah Journal, 2026)
This study aims to analyze the effect of consumptive behavior on the learning commitment of KIP-Kuliah scholarship recipients. A descriptive qualitative approach was used, with data collected through interviews, observation, and documentation and analyzed using the Miles and Huberman model. The findings show that consumptive behavior is influenced by discounts, digital advertising, attractive product displays, peer pressure, and low financial literacy. Scholarship funds are often spent on non-academic needs such as clothing, gadgets, and social activities, causing academic needs to be neglected. This condition leads to decreased learning focus, delayed assignments, increased stress, and lower academic motivation. Therefore, consumptive behavior has a negative impact on students’ learning commitment.